Geometric Modelling in the Narrative of Metropolitan Areas: a View on Attraction Dynamics (diségno, 2023)
The new urban geographies are characterised by a high variety of activities and functions that interact with each other with different complexity, creating polycentric, hierarchical and asymmetrical spatial organisations. The new urban geographies, made up of relationships, force a radical rethinking of mapping, more directed towards the exploration of new intangible realities and freed from the need for cartographic correctness; a voluntary act made up of choices, omissions, additions. Searching for and experimenting with new ways of representing metropolitan complexity, in particular the attractiveness of cities, we arrived at a modelling of three-dimensional geometric surfaces capable of describing the phenomenon with greater emphasis and communicative capacity. The analysis is carried out by adopting a bird’s-eye viewpoint, which, although it tends to generalise by simplifying the complexity of a territorial system, allows its characteristics to be observed and understood globally. The geometric modelling of the attractive phenomenon is the result of a complex graphical-analytical algorithmic procedure based on a hybridisation between graph theory and sophisticated spatial analysis methodologies. The result obtained is a three-dimensional geometric surface of extension equal to the analysis area, whose Einsteinian-inspired morphology deforms as a function of the force of gravity exerted by the metropolis. The case studies are two regions with the main Italian metropolitan areas within them: Rome and Milan.
Keywords: maps; cartography; data visualisation; urban phenomena; metropolitan areas